Aksjomaty, prawo naturalne, wartości i paradygmaty we współczesnych koncepcjach rozwoju - Piontek, Franciszek (Annales. Etyka w Życiu Gospodarczym, 2015)
Contemporary concepts of development (the process of globalization, sustainabledevelopment) can be diversified according to their relation to axioms, natural law,values and paradigms. The subcategories obtained constitute the ground for businessethics. Ethics in business is always needed, however, it can be implementedat-source (as a component of management) or as an end-of-pipe measure. In Poland,constitutional regulations guarantee, indirectly at least, business ethics as a componentof management.